Is National Identity Learned? The Case of Turkish-Cypriot Young Adults in Cyprus - Christos Anagiotos (Adult Education Research Conference, 2014)
Greek-Cypriots and Turkish-Cypriots lived apart from 1974 until 2003 as a result of nationalist conflict on the island. This phenomenological study aims to describe how Turkish-Cypriot young adults (born after 1974) learn their national identity by examining how their lived experiences have influenced this learning.